Palliative care: what’s the evidence? - Sophie Pask; Fliss E.M. Murtagh; Jason W. Boland (Clinical Medicine)
Palliative care is essential for people with an advanced life-limiting illness. Most palliative care is delivered by healthcare professionals who do not specialise in palliative care (‘non-specialists’). Multidisciplinary specialist palliative care services manage more complex problems, providing more comprehensive support when needed.Both ‘non-specialist’ and specialist palliative care improve patient and family outcomes and reduce formal healthcare costs. However, there are inconsistencies in the delivery of, and access to, ‘non-specialist’ and specialist palliative care. These inconsistencies and inequities lead to unrecognised and unmet palliative care needs. There is also inconsistent referral to specialist palliative care services.Unless there are greater resources and training, these issues will be exacerbated by an increasing need for palliative care with changing population demographics.